Predictive long-term asset maintenance strategy: development of a fuzzy logic condition-based control system - Almeida, Fernando Pedro Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence